Potret Peran Perempuan Ciamis dalam Pengentasan Kemiskinan, Pencegahan Stunting dan Pengolahan Pangan Lokal: Narrative Review - Wulandari, Suci; Tupan, Tupan; Wahyu Ari Nugroho, Dwianto (UPT Perpustakaan Universitas Bengkulu, 2025)
This research discusses the important role of women's empowerment in alleviating poverty, preventing stunting, and managing local food in Ciamis Regency, West Java. Women's empowerment in Ciamis Regency has shown a significant contribution in supporting poverty alleviation, stunting prevention and local food management. Various programs, such as entrepreneurship training, nutrition education, and diversification of local food products, have empowered women socially and economically, increased household income, and supported community food security. In preventing stunting, women play a strategic role through nutrition and sanitation education, even though they still face challenges in the form of low public awareness, economic constraints and limited health infrastructure. In the local food management sector, women are involved in developing commodities such as fish, coffee and red chilies, which not only provide added economic value but also strengthen their role as agents of change in the community. Cross-sector support from government, community organizations and local communities has been an important factor in the success of these programs. However, challenges in the form of limited access to resources, social norms and digital literacy need to be overcome to ensure program sustainability. Overall, women's empowerment in Ciamis has great potential to support sustainable development, with a focus on increasing access to resources, education and effective cross-sector collaboration. This initiative makes a real contribution to reducing poverty, increasing food security and strengthening community welfare.